The Role of Bioenergy Utilization of Wastewater in Achieving Sustainable Development Goals for Ukraine - Honcharuk, Inna; Yemchyk, Tetiana; Tokarchuk, Dina; Bondarenko, Valerii (European Journal of Sustainable Development, 2023)
The article is devoted to the issues of Ukraine’s achievement of the Sustainable Development Goals 6. Clean water and sanitation and 7. Affordable and clean energy through bioenergy recycling of wastewater. The purpose of the study was to analyze the current state of wastewater management on the example of Ukraine, as well as to investigate a successful case of bioenergy recycling by a food industry enterprise. The study was based on the principles of sustainable development, circular economy, and scientific research methods: abstract and logical, monographic, graphic and tabular, analysis and synthesis, abstraction, and generalization. The results obtained show that Ukraine has a problem with the safety and quality of drinking water, and wastewater of various origins is a significant pollutant. Among the industrial enterprises of Ukraine, one of the largest consumers of water is the food industry and utilities that belong to the sphere of housing and household services, mainly water utilities. The state of drinking water safety and quality due to pollution remains unsatisfactory. As a result of the study, the authors suggested using bioenergy recycling of wastewater. The authors illustrate a successful case of a particular food industry enterprise in Vinnytsia region, Ukraine, where this practice solved the following problems: 1) pollution of the river by untreated wastewater of the enterprise; 2) energy supply of the enterprise due to biogas from wastewater of its own production, and also additional products - organic fertilizers, which are in great demand in the market. Keywords: recycling, bioenergy recycling, wastewater, sewage sludge, drinking water, biogas, Sustainable Development Goals.